Determinants of the Caregiver Burden of CKD Patients Undergoing Hemodialysis - Faridah, Virgianti Nur; Nursalam, Nursalam; Agustini, Ni Luh Putu Inca Buntari; Lestari, Trijati Puspita; Suratmi, Suratmi; Juanita, Farida; Aris, Arifal (International Journal of Psychosocial Rehabilitation, 2020)
– Families who treat chronic kidney disease (CKD) patients are at risk of experiencing caregiver burden. The family caregiver burden depends on the ability of the families to care for their family members who experience CKD when undergoing hemodialysis. The purpose of this study was to determine the factors associated with the caregiver burden of caring families (primary caregivers). This study used quantitative research and a cross-sectional design. The sample consisted of 95 respondents determined using consecutive sampling from the population in the Hemodialysis room of Muhammadiyah Lamongan Hospital. The variables of this study were caregiver burden (Y), Age (X1), Gender (X2), Educational level (X3), Salary (X4) and Treating the patient’s time (X4). The research instrument consisted of the Zarit Burden Interview (ZBI) method to determine the caregiver burden. Multivariate analysis was done using logistic regression. The results showed that the caregiver model shows a significant burden with a variable in salary and age. The accuracy of the model when predicting caregiver burden was 62.1%. These two variables can explain the burden of the caregivers by 10%. The equation model obtained the results of Caregiver burden= -0,277+0,818*salary-1,313*age (adults)-0,738*age (elderly). There is a need for social support from other families who care. Support system can influence the level of caregiver stress